Reference for normal measurements of psoas muscle among the adult population in Saudi Arabia - Mohammad Abdulrahim Wazzan (Saudi Journal for Health Sciences, 2023)
Background: Psoas muscle measurements and values are generally used to diagnose sarcopenia and evaluate health and well-being. These tests can provide valuable and objective methods to assess patient tolerance to treatments including major surgery, chemotherapy, and physiotherapy. Aim: In this study, we validated the normal measurements and values of the psoas muscle in the adult population of Saudi Arabia. Settings and Design: This study included a retrospective analysis of computerized tomography (CT) studies of 500 adult patients over 18 years of age without any known medical illnesses. Methods: The surface areas and volumes of the psoas muscles on both sides were measured separately on each CT scan in squared centimeters and cubic centimeters (cm3), respectively. The normalized total psoas area (NTPA) was calculated as the total (right and left) psoas area in mm2 normalized to the patient height in meters (m). Statistical Analysis: All statistical analyses were performed using SPSS version 23.0 software (IBM SPSS, Chicago, IL, USA). The Student's t-test was used to evaluate measurement differences between males and females. One-way analysis of variance was used to determine measurement differences due to age. P < 0.001 was considered statistically significant. Results: The psoas muscle values of male participants were significantly higher than those of females. The volumes, surface areas, and NTPAs of the psoas muscles were correlated with patient age and sex. Muscle mass decreased with age, especially after the fifth decade of life, and the highest measurement was observed in the fourth decade of life. The mean psoas muscle surface areas at the lumbar vertebra 4 (L4) level measured 14.0 ± 3.4 cm2 and 7.5 ± 2.2 cm2 in the male and female populations, respectively. Furthermore, the mean psoas muscle volumes measured 436.0 ± 140.2 cm3 and 219.1 ± 73.1 cm3 in the male and female populations, respectively. Finally, the total NTPAs measured 995.1 ± 302.9 mm2/m2 and 667.0 ± 538.5 mm2/m2 in the male and female populations, respectively. Conclusion: This study established psoas muscle reference values suitable for defining sarcopenia in the Saudi Arabian population. Our study results suggest that application of these research methods to determine psoas muscle values may enable assessment of future health-care outcomes for individuals. Moreover, the results may be utilized in a unique and constructive way to predict tolerance of patient populations to therapeutic interventions including surgery, cancer treatment, and rehabilitation services.